Best Practice Teaching Experience by Implementing Problem Based Learning Through a Culturally Responsive Teaching Approach In Teaching Procedure Text For The Ninth Grade Students At SMPN 1 Masbagik - Maulidiyatullayli Rizki (Journal of English Education Forum (JEEF), 2026)
Teaching procedure texts in English as a Foreign Language (EFL) classrooms at the junior secondary school level often presents challenges related to student engagement, motivation, and meaningful language use. Procedure text instruction is frequently perceived by students as repetitive and less engaging when learning activities focus mainly on text structure and grammatical forms without meaningful context. This article reports a best teaching practice implementing Problem Based Learning integrated with a Culturally Responsive Teaching approach in teaching procedure texts to ninth grade students at SMP Negeri 1 Masbagik, Indonesia. This best practice employed a descriptive classroom-based approach to document instructional implementation under regular classroom conditions. Learning activities were designed around real-life problems closely related to students’ local culture and daily experiences, particularly traditional food preparation. Students worked collaboratively in heterogeneous groups to analyze contextual problems, organize procedural steps, construct procedure texts, and present their work. Data were collected through classroom observation, student learning artifacts, and teacher reflection, and were analyzed descriptively to capture learning processes and instructional outcomes. The findings indicate that integrating Problem Based Learning with Culturally Responsive Teaching supported active student participation, improved students’ understanding of procedure text structure and language features, and increased students’ confidence during oral presentations. Learning activities grounded in familiar cultural contexts encouraged students to engage more actively and apply procedural language more meaningfully. This best practice demonstrates that culturally grounded, problem-based instruction is feasible and effective within junior secondary school EFL classrooms and offers practical insights for English teachers seeking to design contextualized and student-centered learning.